Models and scientific tools for regulatory purposes: The case of CO2 emissions from light duty vehicles in Europe. (October 2017) - Ciuffo, B.; Fontaras, G.
Abstract: A key question faced by policy makers throughout the world today is how policy can follow and adapt to the fast technological changes, to the increasing complexity of various scientific fields and to new practices appearing as a result of an increasingly interconnected world. In a rapidly developing and changing landscape, traditional policy making approaches and policy options should be reconsidered in order to provide the optimal benefits to society. A typical example is the field of vehicle fuel consumption and CO2 emissions in Europe. Modern vehicle technologies are changing fast and policy instruments regulating their design should evolve accordingly in order to remain updated. In this context Europe has recently upgraded the emission test procedure for the type-approval of light duty vehicles by adopting the new WLTP (Worldwide Harmonized Light duty vehicle Test Procedure). In order to accelerate its introduction a new modelling tool had to be introduced in the certification process together with new software based instruments, which had to be developed and implemented. This case could open the path to fully software-based vehicle certification in which modelling tools might be applied to reduce the current opportunities of manipulations offered by physical tests. Highlights: The use of models for regulatory purposes is still very limited. Improving the vehicle type-approval in Europe required the development of CO2 MPAS. CO2 MPAS is a vehicle simulation model to calculate CO2 and energy/fuel consumption. CO2 MPAS will be used until 2020 in the type-approval of any LDV in Europe. In the future vehicle energy and fuel consumption may be certified via simulation.